DESIGN AND IMPLEMENTATION OF INTEGRATED INTELLIGENT CONTROLLER FOR PREVENTION AND DETECTION OF ACCIDENT USING IoT AND VANET ASSISTED COMMUNICATION (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The advancement of microelectronics and webbased communication are making a good space in various avenues of human comfort. Though the advanced transport systems prove to be a boon to mankind, the same has also been a disaster and tragedy when it comes to fatal accidents accompanied by huge loss of life and property. This loss is predominant when medical services and family members are not getting accidental information on time. The objective of this proposal is to design a working prototype of intelligent and integrated safety system to public and private vehicles in Oman, to prevent road accidents by alerting the driver under abnormal conditions and if incase of accident, thedetailed information related to the accident is shared with the nearest hospitals, ROP stations and pre-stored numbers will be shared very quickly through Vehicular ad-hoc networks (VANET) in IoT Platform. This early detection is possible by continuously monitoring the important parameters of the vehicle through inbuilt sensors embedded with IOT (internet of things Technology) and this data is continuously compared with the standard information, the deviated values are shared to the main server through a cloud service. The location of the vehicle will be tracked consistently through GPS system. A GSM/GPRS system is used to send an alert message, if the location is a no network area, a RFmodule is used to transmit the alert information and is received by the moving vehicle having this system within the range of RF Module, and this is sent to the next moving vehicle and this process will continue like a chained seriesuntil the vehicle in the network area will receive this message. As soon as the message is received by the vehicle in network area, the alert message will be transmitted to the base station of the VANET